Enhancing Speaking Skills Through Voice Notes in WhatsApp Groups: A Case Study of Non-English Lecturers in Academic Communication - Muhammad Rafi’i; Khairun Niswa (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
In the era of globalized higher education, effective English communication has become essential for academic professionals, including those from non-English disciplines. Nevertheless, non-English lecturers frequently face obstacles in developing spoken proficiency due to limited opportunities for practice, elevated anxiety levels, and inadequate access to formal language training. This case study investigates the use of WhatsApp voice notes as a pedagogical tool to support English-speaking development among non-English lecturers at a private university in Indonesia. Over a six-week intervention, seven lecturers from diverse academic backgrounds participated in structured voice-based tasks and engaged in asynchronous peer interactions via WhatsApp. Data were collected through voice recordings, semi-structured interviews, and reflective journals. Findings indicate that the use of WhatsApp voice notes created a flexible, low-pressure environment conducive to gradual improvements in fluency and communicative confidence. Participants reported reduced speaking anxiety, increased willingness to engage in English, and greater clarity in articulating academic ideas. Moreover, peer feedback and interaction fostered a sense of community and collaborative learning. This study contributes to the Mobile-Assisted Language Learning (MALL) literature by illustrating the potential of widely accessible, low-cost digital tools to facilitate oral language development among professional adult learners. The implications extend to language policy, faculty development, and the design of scalable speaking interventions within higher education institutions